Treaties and alliances of the world : an international survey covering treaties in force and communities of states. ([New York] : Keesing's Publications : Charles Scribner's Sons, 1974)
The bulk of the information can be found in Keesing's contemporary archives.
Keywords: Alliances; Treaties; Treaties